The impact of fiqh muasarah on islamic banking and finance: case studies from the Islamic world / Muhammad Irfan Imaduddin Azran … [et al.] - Azran, Muhammad Irfan Imaduddin; Ramli, Muhammad Adi Irfan; Sallehudin, Sadiq Najwan; Zuhairi, Muhammad Amir Iqbal; Hamzah, Amirul Khalis (2023)
The principles of Fiqh Muasarah, commonly referred to as social jurisprudence, have emerged as a pivotal influence in shaping the ethical and operational landscape of Islamic banking and finance. These principles offer a distinctive perspective on the financial system, emphasizing social responsibility, justice, and equitable wealth distribution within the framework of Islamic law. As the Islamic finance industry gains prominence on the global stage, understanding the impact of Fiqh Muasarah becomes imperative, not only for industry practitioners but also for scholars seeking to grasp the multifaceted nature of this economic system.